LABOR MIGRATION FROM TAJIKISTAN AND ITS ECONOMIC IMPACT - KURBANOV, Sobir (CENTRAL ASIA AND THE CAUCASUS, 2006)
iDfferences in economic development levels and the level of income can be regarded as the main driving force behind labor migration processes.In the past, in the conditions of an administrative-command socialist economy, the labor market developed in the context of integrated national economic planning and the formation of territorial economic complexes. At that time, emphasis was placed on the development of extensive, resource-consuming lines of production, on the construction of industrial giants with ramified and strictly determined links with suppliers from other republics of the former Soviet Union. As a rule, these enterprises had a large workforce, i.e., an excess of labor, whereas economic efficiency and labor productivity remained low.In the 1960s-1990s, programs for the distribution of the productive forces and economic zoning drawn up by the U.S.S.R. State Planning Committee (Gosplan) for the Tajik Soviet Socialist Republic and the region as a whole provided for rapid development of certain sectors of industry, the creation of the South Tajik Territorial Complex, and the construction of engineering, food processing, textile and nonferrous metallurgical plants, which made it necessary to attract skilled labor and to create a system of specialized secondary, vocational and higher education institutions. In accordance with the socioeconomic priorities of that period, specialists in the respective fields were sent to the republic from other parts of the single country in a centralized manner, and local personnel were trained as well.